“Le Tétraque se perdait dans un rêve”: Concordance between Flaubert’s Hérodias and Hérodiade by Milliet, Grémont and Massenet - Clair Rowden (Flaubert: Revue Critique et Génétique)
Commentators have traditionally downplayed the the links between the opera Hérodiade (Millet, Grémont and Massenet, 1881) and Flaubert’s “conte” Hérodias (1877). However, if the two works are viewed through the wider lens of two contextual issues – social and moral debate about the place of religion in Republican society, and the positivist theology of Ernest Renan’s La Vie de Jésus – the links between Massenet’s opera and Flaubert’s tale come into much clearer focus. This article, therefore, demonstrates how and where the opera libretto reflects both Flaubert’s prose and his wider views on Republican society, and how these notions are supported in Massenet’s music. Attention is focussed on the “Dance of the Seven Veils”, recreated by innumerable dancers and musicians, particularly in the wake of Oscar Wilde’s Salomé (1893), but whom inevitably returned to Flaubert’s description of the dance as a naturalist source of inspiration which Wilde’s symbolist text was lacking. While Massenet’s opera has always been identified as lacking a dance scene equivalent to the “Dance of the Seven Veils”, this article argues that Hérode’s Act II aria “Vision fugitive” may be read as a drug-induced hallucinatory dance of Salomé before a sexually aroused yet solitary Hérode. In this light, Massenet’s opera provides a dance scene that moves beyond the traditional voyeurism of Salomé’s dance to provide an erotic, even pornographic scene, despite and due to the absence of a dancer, which evokes Third-Republican concerns – onanism, sterility, depopulation and decadence – as part of the opera’s wider exploration of the place of religion and moral philosophy in society, both ancient and modern.